Correlation between structural, ferroelectric, piezoelectric and dielectric properties of Ba0.7Ca0.3TiO3-xBaTi0.8Zr0.2O3 (x = 0.45, 0.55) ceramics. Issue 17 (1st December 2018) - Keswani, Bhavna C.; Patil, S.I.; James, A.R.; Kolekar, Y.D.; Ramana, C.V.
Abstract: We report on the correlation between structural, ferroelectric, piezoelectric and dielectric properties of the (1-x) Ba0.7 Ca0.3 TiO3 - x BaTi0.8 Zr0.2 O3 ( x  = 0.45, 0.55; abbreviated as 55BCT30 and 45BCT30) ceramics close to morphotropic phase boundary (MPB) region. The 55BCT30 and 45BCT30 ceramics were synthesized by the standard, high-temperature solid state ceramic method. X-ray diffraction (XRD) along with Rietveld refinement indicate that the 55BCT30 ceramics exhibit rhombohedral ( R, space group R 3 m ), orthorhombic (O, space group Amm 2) and tetragonal (T, space group P 4 mm ) phases while 45BCT30 ceramics exhibit only T and O phases. The temperature dependent Raman spectroscopy measurements confirm the structure and phase transformations observed from XRD. All the ceramics are chemically homogeneous and exhibit a dense microstructure with a grain size of 5–7 µm. The presence of polarization-electric field and strain-electric field hysteresis loops confirm the ferroelectric and piezoelectric nature of the ceramics. The polarization current density-electric field curves show the presence of two sharp peaks in opposite directions indicating the presence of two stable states with opposite polarity. Higher values of direct piezoelectric coefficient ( d 33 ~ 360 pC/N) were observed due to the existence of low energy barrier near MPB region and polymorphism. The 55BCT30 ceramics exhibit a higher value of electrostrictive coefficient ( Q 33 ~ 0.1339 m 4 /C 2 ) compared to the well-known lead-based materials. The temperature dependent dielectric measurements indicate the O to T phase transition for 55BCT30 and 45BCT30. These ceramics exhibit a Curie temperature (Tc ) of 380 K with a dielectric maximum of ~ 4500.